Parenting and youth sexual risk in context: The role of community factors. (June 2017) - Goodrum, Nada M.; Armistead, Lisa P.; Tully, Erin C.; Cook, Sarah L.; Skinner, Donald
Abstract: Black South African youth are disproportionately affected by HIV, and risky sexual behaviors increase youths' vulnerability to infection. U.S.-based research has highlighted several contextual influences on sexual risk, but these processes have not been examined in a South African context. In a convenience sample of Black South African caregivers and their 10-14-year-old youth ( M age  = 11.7, SD  = 1.4; 52.5% female), we examined the relation between parenting and youth sexual risk within the context of community-level processes, including neighborhood quality and maternal social support. Hypotheses were evaluated using structural equation modeling. Results revealed that better neighborhood quality and more social support predicted positive parenting, which in turn predicted less youth sexual risk. There was a significant indirect effect from neighborhood quality to youth sexual risk via parenting. Results highlight the importance of the community context in parenting and youth sexual risk in this understudied sample. HIV prevention-interventions should be informed by these contextual factors.